Melting and solidification of thermoplastic polyurethanes as a function of nucleating agents. Issue 3 (13th August 2021) - Stribeck, Almut; Eling, Berend; Pöselt, Elmar; Malfois, Marc; Schander, Edgar
Abstract: The solidification of two thermoplastic polyurethanes (TPU) appears as a two‐stage segregation (large‐scale allocation of hard‐phase entities, short‐scale granulation in the allocated entities). Following consolidation may raise the hard‐phase fraction. Mechanical stability requires the granular morphology. Good nucleating agents (NA) raise the solidification temperature and shorten the lifetimes of allocation and granulation. They can suppress consolidation. Shorter allocation causes lower hard phase fraction, shorter granulation means earlier transition to the solid. Annealed materials have much higher hard phase contents and a morphology of more uniform hard domains in a more regular arrangement. Both TPUs have a hard segment content of ≈ 30 % ≈ 30% but different soft segments (polyether, polyester). Samples are injection‐molded and annealed. Melting‐and‐solidification experiments ( | T ̇ | = 20 K min − 1 |T|=20 K min^-1, T max = 220 ∘ C T_=220 ^° C, Δ T = 1 K Δ T=1 K ) are monitored by small‐angle (SAXS) and wide‐angle X‐ray scattering. Three NAs contain resonating aromatic structures, the fourth is talc. NAs do not affect the melting of polyether TPU, but some NAs raise the melting point of polyester TPU considerably. SAXS chord‐distribution analysis reveals that the region of the melt is framed by segregation peaks. There, the mean chord lengths of the hard phase are the longest and the width of the distributions changes the fastest. Abstract : Monitored by X‐ray scattering, the solidification of two thermoplastic polyurethanes appears as a two‐stage segregation consisting of a large‐scale allocation of big hard phase entities in a heterogeneous melt, followed by granulation of the allocated entities on a short scale. Good nucleating agents raise the solidification temperature and shorten the lifetimes of allocation and granulation.